2017
DOI: 10.1039/c7ce00956a
|View full text |Cite
|
Sign up to set email alerts
|

Nickel(ii) metal–organic frameworks with N,N′-di(4-pyridyl)-naphthalenediimide ligands: influence of secondary building unit geometry on dimensionality and framework dimensions

Abstract: When Ni(NO3) 2•6H2O and N,4,5, are reacted, a one-dimensional coordination polymer (1) is formed. However, reaction with either terephthalic acid (2) or 2,6-naphthalenedicarboxylic acid (3) affords two-dimensional, pillared metal-organic frameworks. 2 and 3 containing rectangular voids of different dimensions which are dictated by the carboxylate ligand and the arrangement of the [M(k 2 -O2NO)]2(µ 2 -O2CR)2] secondary building unit (SBU) that forms the nodes of the framework. The role of SBU geometry, intermol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…This may be caused from conjugate interactions between bdc and dpNDI ligands. Aforementioned numerical results agree with the data that were depicted in the Neil R. Champness's report . Figure b shows the PXRD pattern of [Zn 2 (bdc) 2 (dpNDI)] n .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This may be caused from conjugate interactions between bdc and dpNDI ligands. Aforementioned numerical results agree with the data that were depicted in the Neil R. Champness's report . Figure b shows the PXRD pattern of [Zn 2 (bdc) 2 (dpNDI)] n .…”
Section: Resultssupporting
confidence: 86%
“…Aforementioned numerical results agree with the data that were depicted in the Neil R. Champness's report. [15] Figure 1b shows the PXRD pattern of [Zn 2 (bdc) 2 (dpNDI)] n . All the recorded diffraction peaks are in good accordance with literature reports.…”
Section: Chemical Composition and Morphology Of [Zn 2 (Bdc) 2 (Dpndi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different kinds of N‐containing linkers, bipyridine and their derivatives are widely employed in the construction of versatile MOFs with promising properties . In addition, it has been reported that some MOFs were constructed from rigid dicarboxylate and functionalized bipyridine by the mixed‐ligand strategy, which have intriguing structures and excellent properties . 2,5‐Bis(4‐pyridyl)thiazolo[5,4‐ d ]thiazole (Py 2 TTz) with rigid π‐conjugated system has good luminescence property , .…”
Section: Introductionmentioning
confidence: 99%
“…1,4,5,8-Naphthalenediimide (NDI) derivatives are photoactive moieties to construct photochromic MOFs due to the features of NDIs; NDIs can act as redox-active units that undergo reversible single one-electron reduction to form NDI radical anions for photoinduced electron transfer. Several studies have been focused on NDI-based MOFs to date, but only a few of them have investigated their photochromic properties, the porosity, structural topology, and π–π stacking of NDI-based MOFs, which may influence the charge transfer. Furthermore, MOFs could be used as absorbent materials for the treatment of dye wastewater due to their tunable pore sizes, shape, functional active sites, and the interactions between MOFs and adsorbates, and these interactions between host–guest frameworks could enhance the selective adsorption property of organic dyes, such as hydrogen bonding interactions, π–π stacking, electrostatic interactions, and Lewis acid–base interactions.…”
mentioning
confidence: 99%